ANALISIS PENYEBAB RENDAHNYA KINERJA ORGANISASI DI PUSKESMAS CANDILAMA KOTA SEMARANG - Nova Listiana; Antono Suryoputro; Ayun Sriatmi (Jurnal Kesehatan Masyarakat (Undip), 2018)
Public Health Centers as public sector organizations that serve the health sector can not be separated from the community's assessment of the increasingly critical of its performance. One of the ways used by Health Office in assessing the success of Puskesmas is by conducting Puskesmas Performance Assessment. Candilama Health Center is one of the urban-type community health centers in Semarang City. Candilama Health Center performance assessment results in the last 4 years starting from 2012 shows a declining trend every year. The purpose of this research is to analyze the factors that are suspected to be the cause of the poor performance of the Candilama Health Center organization. This study is a qualitative research with in-depth interviews to program implementers in Health Center and informants triangulation Head of Puskesmas, Sub Division of Planning and Evaluation of Health Office, Head of Primary Health Service Section of Health Office.The result of the research shows the factors that cause the low performance of Candilama Public Health Center are, the availability of the number and competency of health personnel are still lacking, the supervision process from the Head of Health Center is still not good, the unmistakable leadership of the Head of Health Center in making decisions, work motivation from colleagues and leadership perceived less, and still weak organizational culture at Candilama Community Health Center. To overcome this problem, it is suggested that Candilama Head of Puskesmas can change their leadership style, all employees are expected to build good communication among employees so as to reduce misunderstanding, reward and proper recognition appropriately to employees with achievement of work achieved, and vice versa, also doing recreation together so that all employees feel close to other employees and leaders to further tighten the bonds. Health Office is expected to open the recruitment of health workers who are still lacking in Public Helath Center Semarang City in cooperation with BLUD Puskesmas and willing to provide training to all program implementers in Puskesmas both civil servants and non-civil servants.